Peningkatan Kompetensi dan Pembuatan Teknologi Terbaru Beton Porous di Jurusan Teknik Konstruksi dan Perumahan SMKN 1 Balikpapan - Achmad, Karmila; Sulistyo, Totok; Sunarno, Sunarno; Kiptiah, Mariatul; M. Ain, Mohammad Isram (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
The city of Balikpapan has many flood points every year,.Flood events are a priority issue for the Balikpapan City Government, in 2017 there was an increase in flood events by 89 incidents. To solve this problem is to apply the construction with the latest environmentally friendly technology, namely porous concrete so that surface water can seep into the ground and can become a groundwater reserve. Porous concrete is the latest type of concrete technology with high porosity which is applied as a concrete plate which allows rainwater and water from other sources to pass through. Limited facilities and infrastructure, lack of teaching staff relevant to the Construction and Housing Study Program at SMKN 1 Balikpapan School so that they cannot carry out concrete manufacturing and testing because this is a basic competency that every student must have. The activity began by formulating a program that was relevant to the knowledge and research of the PkM team of the Civil Engineering Department of the Balikpapan State Polytechnic and the problems that exist around Balikpanan City. SMKN 1 Balikpapan to carry out follow-up activities or programs to be implemented, activity planning, activity schedules and activity output. The activities were carried out for 2 days which included socialization and practice of making porous concret.